2013
DOI: 10.1016/j.jembe.2013.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic evidence for local adaptation to heat stress in the marine snail Chlorostoma (formerly Tegula) funebralis

Abstract: Southern California (USA) populations of the intertidal marine snailChlorostoma (formerly Tegula) funebralis generally occupy warmer climates and are exposed to high air temperatures during low tides more often than northern California populations. Available genetic data suggest there is extensive gene flow across a broad range of C. funebralis populations, so it is unclear if populations can adapt to differences in local environments. To test for population-specific responses to heat stress, three phenotypic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 50 publications
2
25
0
Order By: Relevance
“…), few have investigated genetically based population differences in thermal tolerance (but see Kuo & Sanford ; Willett ; Schoville et al . ; Gleason & Burton ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…), few have investigated genetically based population differences in thermal tolerance (but see Kuo & Sanford ; Willett ; Schoville et al . ; Gleason & Burton ).…”
Section: Introductionmentioning
confidence: 99%
“…Across this large latitudinal range, populations experience significantly different maximum, minimum, and average air and water temperatures (National Oceanographic Data Center, NOAA Satellite and Information Service). Gleason & Burton () demonstrated that northern and southern California populations differ significantly in thermal tolerance, with three southern populations consistently suffering significantly lower mortality and recovering significantly more quickly following heat stress compared with three northern populations. However, the molecular mechanisms underlying these differential tolerances have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among many factors such as behavioral, biochemical, physiological, and genetic/epigenetic ones (Boyko and Kovalchuk, 2008;Gleason and Burton, 2013), gene expression changes represent one crucial mechanism for species to cope with environmental stressors during biological invasions (de Nadal et al, 2011). For instance, the transcriptional expression of individual candidate genes (such as the heat shock protein 70 gene) showed different patterns between invasive and native species in response to heat stress, suggesting that a higher level of heat tolerance of invasive species might contribute to their invasion success (Henkel and Hofmann, 2007;Zerebecki and Sorte, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in connectivity may also have implications for management issues such as the design and placement of marine protected areas and networks since the transport of larvae between locations may be essential to maintaining populations (Strathmann et al 2002, Carr et al 2003, Morgan et al 2009). Moving boundaries could also contribute to the ability of larvae from source populations to reach sites, and since populations of marine species may differ greatly in responses to environmental factors such as temperature, movement among populations (or lack thereof) may have important repercussions for how populations respond to perturbations such as climate change (Kelly et al 2012, Sorte et al 2011, Gleason & Burton 2013.…”
Section: Introductionmentioning
confidence: 99%